Consumer Preferences In Choosing Coffee Types (Coffea Sp.) (Case Study In A Coffee Shop In Bandung City) - Didit Hadayanti; Muhammad Irfhan Fajri Royyan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Coffee is a plantation commodity that plays an important role in the Indonesian economy. This role, among others, is that this commodity is estimated to be the main source of income for no less than 1.84 million families, most of whom live in rural areas in remote areas. Coffee is an export commodity that is important for economic growth which is able to contribute quite a large amount of foreign exchange to the Indonesian nation. The aim of this research is to analyze consumer preferences in choosing arabica and robusta coffee types based on consumer characteristics, purchasing patterns and coffee attributes. This research uses descriptive methods. The technique used to collect data in this research is the survey method. This research was conducted at Kedai Kopi Nuansa and Kedai Kopi Bangreng located in Bandung City, the sampling method used the Slovin formula which resulted in 100 respondents from the two coffee shops. Data analysis uses percentages based on the frequency and number of respondents who voted. The research results show that Robusta coffee is a very popular choice among consumers. Factors that influence consumer preferences are consumer characteristics (age, gender and occupation are the dominant factors that differentiate), characteristics of consumer purchasing patterns (lifestyle of consuming coffee, preferred coffee, frequency of purchase and amount of coffee purchased), and characteristics of coffee attributes (aftertaste, price, caffeine effect).